(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article deals with the functioning of the reference in the poetic. The author investigates language means, which help to transfer semantics of address. The special attention addresses on thematic groups of rhetorical references, which use in the poetic texts is connected to the phenomenon of communicative carry.